(untitled) (Applied Biological Research, 2023)
Staphylococcus aureus is a human pathogen of clinical importance related to a variety of infections. The objective of this study was to analyze theepidemiological characteristics of S. aureus obtained from the patients of several hospitalin Tebessa area (East Algeria). This study was made as per the microbiological methods based on morpho-physio-biochemical characters. S. aureus samples (1200) were analyzed, and 250 strains were identified, representing the 20.83% of population. An antibiogram accompanied by screening on oxacillin (6 μg mL-1) made it possible to detect β-lactam resistant strains. Seventy eight (31.2%) methicillin-resistant Staphylococcus aureus (MRSA) strains were isolated. The study revealed that the risk factors like age, nature of sampling and use of β-lactams antibiotics by patients have a relationship with MRSA infection. On the other hand, the presence of MRSA has no relationship with sex factor of hospitalized patients. By comparison with previous studies, it is inferred that in Algeria the carriage of MRSA in the city is worrying. It is necessary to control the diffusion of these strains for the control of epidemics with multi resistant germs.